Pengembangan Sistem Informasi Berbasis Web Buku Kas Umum Satuan Kerja Perangkat Daerah (SKPD) - Yumniati Agustina; Widyat Nurcahyo (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
Financial Management Guidelines in the Regulation of the Minister of Home Affairs No. 13/2006 requires the financial performance reports are decentralized to regional working units (SKPD). In order to meet these needs, the role of computer-based information system is the solution. This study developed a web-based information systems for the financial administration processes in the SKPD, which is related to the making of financial performance reports such as General Ledger and Subsidiary Ledgers. This application is emphasized to minimize human error and increase the accountability of the SKPD's financial performance reports. From the test results, the application can produce a perfect output, and found no significant deficiencies in terms of speed and accuracy of the system. In the future, applications need to be developed by adding adequate security to be used over the Internet.